Mitochondrial Function and Brain Physiological Activities in Ischemic Stroke - Mayevsky, Avraham (Medical Science: Trends and Innovations Vol. 13, 2025)
Stroke or Cerebro Vascular Accident (CVA) is the second cause of death and the 1st cause of patients’ disabilities around the world. The initial event that leads to the occurrence of a Stroke is a sudden disturbance in microcirculatory blood flow and a drop in oxygen supply to the brain tissue. More than 50% of the total energy consumed by the brain is utilised by active transport processes, which are responsible for keeping the ionic homeostasis in the brain. Under an ischemic condition, energy availability is limited, and, as a result, inhibition of the ion pumps is unavoidable. The initial consequence of such inhibition is a gradual accumulation of K+ in the extracellular space, leading to a second phase of the ischemic depolarisation (ID) phenomenon. During ID, extracellular K+ will increase 15- 20 fold, while extracellular Ca2+ will decrease 10 fold. Another optional effect of mild ischemia is the development of Cortical Spreading Depression due to the leakage of K+ into the extracellular space. The Mongolian gerbil provides a very useful animal model to study the effects of ischemia on brain functions. During the last few years, some papers have described the interrelation between mitochondrial function and ischemic stroke. The aims of the study were as follows: (1) To elucidate the mechanism behind the development of ischemic depolarisation or cortical spreading depression under unilateral and bilateral carotid artery occlusion. (2) To correlate the kinetics of the recovery processes to the level of ischemia. We tested the correlation between energy depletion level (evaluated by intra mitochondrial NADH redox state and CBF) and the development of ischemic depolarization (ID) or CSD (evaluated by extracellular K+, H+, Ca2+, DC potential and 366 nm reflectance changes) under partial and complete ischemia using the multiparametric monitoring system (MPA). The results could be summarised as follows: (1) Under bilateral occlusion, in all gerbils, the ID was recorded within 1-2 min. (2) Under unilateral occlusion, the level of ischemia obtained was significantly smaller and led to the ID in about 60% of the gerbils. (3) The K+ leakage during the ID had an 'all or none' nature in terms of maximal K÷ levels and time to reach it. (4) The main effect of various lengths of bilateral occlusion was on the recovery time of the extracellular K+ level. (5) Cortical Spreading Depression (CSD) develops in most cases during the recovery from the ischemic event when ID was not recorded under the ischemic episode. The study concluded that the effects of Brain Ischemia (Stroke) on various functions of the brain are dependent on the duration of decreased levels of oxygen supply. Moreover, the accumulation of potassium in the extracellular space is dependent on the depletion level of the energy supply.